Conceptual design of a slow pyrolysis plant for producing biochar derived from crop residues and agro-industrial cassava wastes. (Revista Sistemas de Producción Agroecológicos, 2025)
Biochar, which is produced from agricultural or agro-industrial waste, is becoming an increasingly interesting by-product. It has various potential applications that could provide profitable alternatives for Colombian producers. This article assesses the feasibility of producing biochar from cassava waste, specifically branches and peels. It explores the potential uses of biochar and evaluates its technical feasibility based on data from the Orinoquia region. The conceptual project is based on laboratory analyses conducted in the pyrolysis laboratory at the Universidad de los Llanos. Different slow pyrolysis treatments were tested, and the biochar samples were evaluated for pH, conductivity, and thermal properties. The results showed that cassava branches produced the highest biochar yield at 41.22%. The technical analysis indicates that establishing a pyrolysis plant for processing branches and peels is feasible in Orinoquia. Thus, biochar is considered a technically viable alternative, as a significant amount of residual biomass is readily available in the cassava production chain. This biomass has potential applications as a biofuel, soil improver, carbon capture agent, and even as electrodes for supercapacitors in the electronics field.
Keywords: Agricultural waste; Biomass valorisation; Orinoquia; Thermochemical process